A review of immunotherapy for bone tumors - Wang, Chenwen; Chen, Zixiong; Mo, Haokun; Wang, Jiang; Zhou, Wei (Frontiers in Immunology, 2025)
This article reviews the latest research progress in immunotherapy for bone tumors. Bone tumors are a serious threat to human health, and traditional treatments have limitations. Recently, immunotherapy, as an emerging treatment method, has shown great potential in the treatment of bone tumors. This article systematically introduces the pathological features, traditional treatment methods and limitations of bone tumors, and focuses on the principles, application status and challenges of immune checkpoint inhibitors, CAR-T cell therapy, tumor vaccines and other immunotherapies. At the same time, the combined application strategy of immunotherapy and traditional treatment was discussed, and the future development direction was prospected. The purpose of this article is to provide a reference for the research and clinical application of bone tumor immunotherapy.